Efektivitas Model Pembelajaran Kooperatif Metode TTW (Think, Talk, Write) dan SQ3R (Survey, Question, Read, Recite, and Review) Terhadap Hasil Belajar Geografi dan Kemampuan Geoliterasi Kelas XI IPS MAN 1 Salatiga Tahun Ajaran 2019/2019 (Materi Bonus Demo - Chasanah Karismatika; Singgih Prihadi; Yasin Yusup (Universitas Sebelas Maret (UNS), 2020)
The aims of this research to determine (1) differences of effectivity among the application of TTW, SQ3R, and lecture methods, (2) the effectiveness between the SQ3R method and the lecture method, (3) the effectiveness between the TTW method and lecture method, (4) the effectiveness between the TTW method and the SQ3R method in learning outcomes and the geoliteracy abilityof the XI Socialstudents MAN 1 Salatiga Academic Year 2018/2019.This research is an experimental research (Quasi Experiment) with a pretest-posttest design. The population is the studensts of class XI Social in MAN 1 Salatiga Academic Year 2018/2019. The research sample is cluster random sampling. Data collection techniques using documentation techniques, observation, and tests. The data analysis technique used one-way anava and continued after anava.The results showed that (1) there were differences in learning outcomes and geoliteracy abilities of students in the use of the TTW, SQ3R, and lecture methods, (2) the SQ3R method was more effective than the lecture method on student learning outcomes and geoliteracy skills, (3) the TTW method is more effective than the lecture method on learning outcomes and the geoliteracy of students, (4) there is no difference in learning outcomes and geoliteracy abilities of students in the use of the TTW and SQ3R methods of the class XI Social MAN 1 Salatiga academic year 2018/2019.